(4 целых 1/3 минус 3 целых 4/9 )в квадрате × ( 2 целых 1/4) в квадрате с разяснением

Vanysik Vanysik    2   03.11.2019 15:57    11

Ответы
csnoleg csnoleg  10.10.2020 11:07

Пошаговое объяснение:

\tt\displaystyle {\left( {4\frac{1}{3}-3\frac{4}{9}}\right)^2}*{\left( {2\frac{1}{4}} \right)^2}={\left( {4\frac{3*1}{3*3}-3\frac{4}{9}} \right)^2}*{\left({2\frac{1}{4}}\right)^2}={\left( {4\frac{3}{9}-3\frac{4}{9}} \right)^2}*{\left({2\frac{1}{4}}\right)^2}={\left( {3\frac{{12}}{9}-3\frac{4}{9}} \right)^2}*{\left({2\frac{1}{4}}\right)^2}={\left( {\frac{8}{9}} \right)^2}*{\left( {\frac{9}{4}}\right)^2}=\frac{{{8^2}}}{{{9^2}}}*\frac{{{9^2}}}{{{4^2}}}=\frac{{{8^2}}}{{{4^2}}}=\frac{{{{\left( {{2^3}} \right)}^2}}}{{{{\left( {{2^2}} \right)}^2}}}=\frac{{{2^6}}}{{{2^4}}}={2^{6-4}}={2^2}=\boxed4

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Математика